2017
DOI: 10.1002/2016jc012241
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two eddies: The biophysical characteristics of two contrasting cyclonic eddies in the East Australian Current System

Abstract: Mesoscale cyclonic eddies are known to be highly productive. Less well‐known are the dynamics and productivity of smaller cyclonic eddies, known as frontal eddies, that form on the landward side of western boundary currents. In this study, we investigate the physical and biogeochemical properties of two contrasting cyclonic eddies in the East Australian Current (EAC). The first (“Murphy”), a mesoscale cyclonic eddy that formed at ∼28°S with a diameter of ∼160 km and high surface chlorophyll‐a concentrations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 62 publications
6
49
0
Order By: Relevance
“…The vorticity, radius, and distribution of mesoscale eddies diagnosed with weekly merged altimetry fields (Everett et al, ; Pilo, Mata, & Azevedo, ) are similar to those identified in our study. Individual mesoscale eddies in the region studied with models (Macdonald et al, , Oke & Griffin, ) and more recently observed (Roughan et al, ) also lie within the realm of eddies presented here.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The vorticity, radius, and distribution of mesoscale eddies diagnosed with weekly merged altimetry fields (Everett et al, ; Pilo, Mata, & Azevedo, ) are similar to those identified in our study. Individual mesoscale eddies in the region studied with models (Macdonald et al, , Oke & Griffin, ) and more recently observed (Roughan et al, ) also lie within the realm of eddies presented here.…”
Section: Discussionsupporting
confidence: 76%
“…This study is based on a numerical simulation with a spatial resolution of (1/10)°. Submesoscale and small mesoscale features that are not resolved at this spatial resolution may modify the retention time; nevertheless, the median retention times we find are the same order of magnitude than those obtained from observations of two‐dimensional current fields, specifically from drifter releases inside large and small eddies in the region (~163 and ~35 km in diameter, respectively, Roughan et al, ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the submesoscale range, cyclonic frontal eddies have been observed in high frequency (HF) ocean radar maps, propagating poleward inshore of the EAC, irregularly timed but on average one per week, with inshore radii of ∼10 km (Schaeffer et al, ). These small‐scale eddies are associated with Rossby numbers of order 1 and intense, asymmetrical vorticity and divergence fields (Mantovanelli et al, ), and high productivity (Roughan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the East Australian Current (EAC), the WBC of the South Pacific, there has been several studies on the properties and dynamics of eddies (e.g., Roughan et al, ; Rykova et al, ; Rykova & Oke, ), the interaction of eddies with other eddies (Cresswell & Legeckis, ), the mean flow (e.g., Mata et al, ; Nilsson & Cresswell, ), and the ocean bottom (e.g., Oke & Griffin, ), and the impact of eddies on productivity (e.g., Everett et al, ) and marine biota (e.g., Suthers et al, and references therein). However, only one study describes the vertical circulation within an eddy in the EAC region.…”
Section: Introductionmentioning
confidence: 99%